Wind: Pathosformel and Iconology of a Quintessence - Baert, Barbara (Eikón / Imago, 2014)
The representation, evocation and suggestion of wind in the visual arts touche on fundamental ideas relating to the anthropology of the senses and their descent into the visual medium. How has wind impregnated the theory of the image? Is it a question of visual pneuma? And is wind in the arts a question of content, or rather a matter of formal affect?